Deep Margin Elevation in Contemporary Restorative Dentistry: A Narrative Review - Kawono; Thelessy, Olivia (Dentika: Dental Journal, 2025)
Deep subgingival margin is a cause of persistent challenges in restorative dentistry, due to obstructing adhesive methods, compromising periodontal health, and limiting long-term efficacy. Therefore, this narrative review aims to examine Deep Margin Elevation (DME) as a minimally invasive substitute for surgical crown lengthening. The objective is to amalgamate biological and restorative principles, assess material and adhesive methodologies, and pinpoint areas requiring additional investigation. DME is the coronal repositioning of subgingival margin using resin-based restorative materials to enhance visibility, isolation, and marginal adaptability. Recent evidence shows that DME improves fracture resistance, marginal sealing, and periodontal compatibility, while conserving tooth structure and minimizing patient morbidity relative to surgical interventions. The results are affected by operator proficiency, material choice, and procedural discrepancies. The limited availability of randomized trials and the absence of established recommendations continue to pose substantial obstacles. DME presents a promising conservative strategy designed for minimally invasive dentistry. However, the extensive implementation shows a need for substantial proof and agreed-upon guidelines.